The Effect of Training, Career Development, and Job Satisfaction on Employee Performance at the West Java Settlement Infrastructure Center - Astuti, Ludwi (Dinasti International Journal of Digital Business Management, 2025)
The purpose of this study was to determine the effect of training, career development and job satisfaction on employee performance at the West Java Settlements Infrastructure Center. The questionnaire instrument was tested using validity and reliability tests. The regression used was multiple linear regression with the t-test, and processed using SPSS software. The population in this study was 36 employees, all of whom were used as samples, so that the population was the same as the sample, which was 36 respondents (saturated sampling method). This study is a quantitative study. The data was analyzed using descriptive statistical analysis. The results show that the training variable (X1) obtained tcount> ttable (1.412) < (1.693), career development variable (X2) tcount> ttable (2.206)> (1.693) and job satisfaction variable (X3) tcount> ttable (2.474)> (1.693). So partially training, career development and job satisfaction have a positive and significant effect on employee performance. While simultaneously training, career development and job satisfaction have a simultaneous and significant effect.